1991
DOI: 10.1037/0033-3204.28.3.480
|View full text |Cite
|
Sign up to set email alerts
|

"Dichos" as metaphorical tools for resistant Latino clients.

Abstract: are cultural metaphors which may be used to illustrate psychotherapeutic principles as applied to specific cultural groups. The author describes the use of such tools and gives several clinical examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…Clinicians working with Latino populations have found that the use of 'dichos ' or 'refranes' */popular Spanish proverbs */can create the appropriate cultural ambience to discuss popular beliefs, social norms and their effect on people's lives (Aviera, 1996;Zuñ iga, 1991Zuñ iga, , 1992. Dichos may also have a place in HIV prevention interventions.…”
Section: A Randomized Controlled Trial To Test An Hiv-prevention Intementioning
confidence: 98%
“…Clinicians working with Latino populations have found that the use of 'dichos ' or 'refranes' */popular Spanish proverbs */can create the appropriate cultural ambience to discuss popular beliefs, social norms and their effect on people's lives (Aviera, 1996;Zuñ iga, 1991Zuñ iga, , 1992. Dichos may also have a place in HIV prevention interventions.…”
Section: A Randomized Controlled Trial To Test An Hiv-prevention Intementioning
confidence: 98%
“…As short, traditional guides of conduct, dichos endorse moral and ethical values (Delgado-Gaitán 2004) as well as transmit cultural values and beliefs to younger generations by teaching lessons about life, offering advice, summarizing ideas, and expressing a specific perspective on a given situation (Chahin et al 1999;Zuñiga 1992). These metaphorical images of Hispanics' cultural values and beliefs are spontaneous, brief, and often developed with rhyme (Zuñiga 1991(Zuñiga , 1992. Dichos are funds of knowledge of a people, and are part of the historically accumulated body of knowledge essential for household functioning and well-being among native speakers of Spanish (Gonzalez et al 2001;Moll 1992).…”
Section: Dichosmentioning
confidence: 99%
“…Dichos are funds of knowledge of a people, and are part of the historically accumulated body of knowledge essential for household functioning and well-being among native speakers of Spanish (Gonzalez et al 2001;Moll 1992). Most of the published literature on dichos available to date comes from the field of counseling psychology, where dichos have been explored to enhance counseling approaches with Hispanic Spanishspeaking clients (Altarriba and Santiago-Rivera 1994;Iterian and Diaz-Martinez 2006;Zuñiga 1991Zuñiga , 1992. Given their cultural and linguistic relevance among Hispanics, dichos may encourage family storytelling.…”
Section: Dichosmentioning
confidence: 99%
“…The perspectives and wisdoms of dichos emanate from patrónes which have been passed across generations and a means of conocimiento translated into life lessons. Capturing the sabiduría of Latina/os (Comas-Díaz, 2006) and serving as concrete directives from patrónes, dichos illuminate pathways to move through difficult experiences as they accentuate ability, resilience, and endurance (Castellanos & Gloria, 2014;Zuniga, 1991). Comas-Díaz (2006) aptly argued that dichos can "offer subversive strategies as they express adaptive responses to oppression, colonization, and internalized oppression" (p. 444).…”
Section: Living Through Dichos: the Bridge Between Ancestral Teachingmentioning
confidence: 99%